An investigation into equivalence in Vietnamese translation of English idioms with words denoting body parts in American short stories - Trương Thị Thuỳ Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
There have a large number of idioms related to body parts in both English and Vietnamese. This thesis investigated English idioms with words denoting the human body parts (IWDHBPs) and their equivalents. Absolute equivalences, Partial equivalence with same meanings but the elements of body parts removed/ changed, partial equivalence with literal meanings of body parts and non-equivalence were discussed in this thesis. Idioms share cultural and historical information and broaden people’s understanding and manipulation of a language. It is, therefore, necessary for translators to try their best to pursue the most proper way of translating them. Only with proper translation strategies can the human body idioms be translated with the national features and convey the meaning of the original. This thesis entitled ‘An investigation into equivalence in Vietnamese translation of English idioms with words denoting body parts in American short stories” focused on analyzing Vietnamese and English idioms with words denoting the human body parts (IWDHBPs), providing the general understanding and introduction to the source and characteristics of English idioms and generally comparing Vietnamese and English IWDHBPs. The semantic and syntactic features of idioms were also discussed in this thesis. Using comparison and contrast method, the paper attempts to point out the equivalent and non-equivalent references of human body part idioms found in the English novels and their Vietnamese translation. Practically, this thesis aims at providing students and teachers with necessary information so that they can benefit in their learning and teaching English, particularly in the field of translation. Furthermore, suggestions to solve the problem as well as implications for teaching idioms are also given.